Examining the benefit of a higher maintenance dose of extended-release buprenorphine in opioid-injecting participants treated for opioid use disorder - Mark K. Greenwald; Katharina L. Wiest; Barbara R. Haight; Celine M. Laffont; Yue Zhao (BMC, 2023)
Abstract Background BUP-XR (SUBLOCADE®) is the first buprenorphine extended-release subcutaneous injection approved in the USA for monthly treatment of moderate-to-severe opioid use disorder (OUD). Among patients with OUD, those who inject or use high doses of opioids likely require higher doses of buprenorphine to maximize treatment efficacy. The objective of this analysis was to compare the efficacy and safety of 100-mg versus 300-mg maintenance doses of BUP-XR in OUD patients who inject opioids. Methods This was a secondary analysis of a randomized, double-blind, placebo-controlled study in which adults with moderate or severe OUD received monthly injections of BUP-XR (2 × 300-mg doses, then 4 × 100-mg or 300-mg maintenance doses) or placebo for 24 weeks. Abstinence was defined as opioid-negative urine drug screens combined with negative self-reports collected weekly. Each participant's percentage abstinence was calculated after the first, second, and third maintenance doses in opioid-injecting and non-injecting participants. The proportion of participants achieving opioid abstinence in each group was also calculated weekly. Treatment retention rate following the first maintenance dose was estimated for opioid-injecting participants with Kaplan-Meier method. Risk-adjusted comparisons were made via inverse propensity weighting using propensity scores. Buprenorphine plasma concentration-time profiles were compared between injecting and non-injecting participants. The percentages of participants reporting treatment-emergent adverse events were compared between maintenance dose groups within injecting and non-injecting participants separately. Results BUP-XR 100-mg and 300-mg maintenance doses were equally effective in non-injecting participants. However, in opioid-injecting participants, the 300-mg maintenance dose delivered clinically meaningful improvements over the 100-mg maintenance dose for treatment retention and opioid abstinence. Exposure-response analyses confirmed that injecting participants would require higher buprenorphine plasma concentrations compared to non-injecting opioid participants to achieve similar efficacy in terms of opioid abstinence. Importantly, both 100- and 300-mg maintenance doses had comparable safety profiles, including hepatic safety events. Conclusions These analyses show clear benefits of the 300-mg maintenance dose in injecting participants, while no additional benefit was observed in non-injecting participants relative to the 100-mg maintenance dose. This is an important finding as opioid-injecting participants represent a high-risk and difficult-to-treat population. Optimal buprenorphine dosing in this population might facilitate harm reduction by improving abstinence and treatment retention. Trial registration: ClinicalTrials.gov, NCT02357901.